Avaliação do potencial alelopático de raízes de capim annoni-2 (Eragrostis plana Nees) e estudo fitoquímico - Silva, Mayara Gobetti Fernandes da (2014)
The Grass Annoni-2 (Eragrostis plana Nees), considered a noxious invasive and difficult to eradicate plant has the capacity to dominate the environment they are in, superseding Agrieconomic and native species. Part of this ability is related to allelopathic effects caused by allelochemicals released by this species. Thus, the identification of these allelochemicals can be a good alternative for the production of bio-herbicides. In this study, we determined the allelopathic potential of crude extracts of petroleum ether, ethyl acetate and methanol from the root of E. plana Nees collected in the summer in the experimental area of the course of Agronomy UTFPR - Pato Branco campus, as well as a phytochemical study for structural elucidation of potential allelochemicals. The allelopathic potential was assessed from bioassays of germination and growth of radicle and hypocotyl, using two receptor species (Ipomoea grandifolia and Euphorbia hetetophylla) and three concentrations of crude extracts (200, 400 and 600 ppm). As a result it was found that crude extracts of petroleum ether and ethyl acetate act mainly on the kinetics of the germination process by slowing it, while the crude methanol extract worked, especially in reducing the germination inhibiting 75.4% in comparison with blank (distilled water), causing deformities, and even death of seedlings these data to the recipient E. heterophylla, most affected. Regarding the growth bioassay hypocotyl and radicle, crude methanol extract was the least effective, highlighting the crude extract of petroleum ether at 600 ppm against receiving I. grandifolia species, causing a decrease in the growth of radicle and hypocotyl 66.3% and 65.5%, respectively, and the crude ethyl acetate extract also receiving 600 ppm against E. heterophylla caused a decrease of 63.6% and 72% of the length of the hypocotyl and radicle respectively, both compared with their white (distilled water). Through phytochemical study was proposed structure of a diterpene, through the fractionation and purification of the crude extract of petroleum ether, and a compound whose structure has not been fully elucidated, this from crude methanol extract. The allelopathic effects shown by the roots of the grass Annoni-2, were quite effective, these can be attributed to the isolated phytotoxic substances in this study.